The impact on hospital resource utilisation of treatment of hepatic encephalopathy with rifaximin‐α. (5th April 2016) - Orr, James G.; Currie, Craig J.; Berni, Ellen; Goel, Anurag; Moriarty, Kieran J.; Sinha, Ashish; Gordon, Fiona; Dethier, Anne; Dillon, John F.; Clark, Katie; Richardson, Paul; Middleton, Paul; et al.
Abstract: Background & Aims: Rifaximin‐α reduces the risk of recurrence of overt hepatic encephalopathy. However, there remain concerns regarding the financial cost of the drug. We aimed to study the impact of treatment with rifaximin‐α on healthcare resource utilisation using data from seven UK liver treatment centres. Methods: All seven centres agreed a standardised data set and data characterising clinical, demographic and emergency hospital admissions were collected retrospectively for the time periods 3, 6 and 12 months before and following initiation of rifaximin‐α. Admission rates and hospital length of stay before and during therapy were compared. Costs of admissions and drug acquisition were estimated using published sources. Multivariate analyses were carried out to assess the relative impact of various factors on hospital length of stay. Results: Data were available from 326 patients. Following the commencement of rifaximin, the total hospital length of stay reduced by an estimated 31–53%, equating to a reduction in inpatient costs of between £4858 and £6607 per year. Taking into account drug costs of £3379 for 1‐year treatment with rifaximin‐α, there was an estimated annual mean saving of £1480–£3228 per patient. Conclusions: Initiation of treatment with rifaximin‐α was associated with a marked reduction in the number of hospital admissions and hospital length of stay. These data suggest that treatment of patients with rifaximin‐α for hepatic encephalopathy was generally cost saving. Abstract : See Editorial on Page1252